Needs for family caregivers of Cerebrovascular Accident survivors - Jaine Kareny da Silva; Karla Ferraz Anjos; Jeorgia Pereira Alves; Darci de Oliveira Santa Rosa; Rita Narriman Silva de Oliveira Boery (Universidad de Antioquia, 2020)
Objective. To know the needs of family caregivers of Cerebrovascular Accident survivors. Methodology. This is a qualitative, descriptive, and exploratory study. Data were collected from 37 family caregivers of Cerebrovascular Accident survivors from a city in the interior of Bahia, through an interview using a semi-structured form, between September 2017 and March 2018, and submitted to thematic content analysis. Results. Three categories emerged: the early need for health education on the disease and care for family caregivers; the need to restructure care for family caregivers; 3) family caregivers need free time for social activities and (self)care. Conclusion. Caregivers have basic needs for health care and social interaction, which can enable by educational health interventions.